Bir dostluk öyküsü : belgelerle Türk-Japon ilişkileri = Aru yûkō no shōsetsu : shîryōde shōmeisareru nichito no kankei = A Friendship story : Turkish-Japanese relations with the documents (Kayseri)
277 s.